Cytosolic DNA accumulation promotes breast cancer immunogenicity via a STING-independent pathway - Jing Zhang; Hui Dai; Jared K Burks; Shiaw-Yih Lin; Daniel J McGrail; Lei Huo (Journal for ImmunoTherapy of Cancer, 2023)
Background Immune checkpoint blockade (ICB) has revolutionized cancer treatment. However, ICB alone has demonstrated only benefit in a small subset of patients with breast cancer. Recent studies have shown that agents targeting DNA damage response improve the efficacy of ICB and promote cytosolic DNA accumulation. However, recent clinical trials have shown that these agents are associated with hematological toxicities. More effective therapeutic strategies are urgently needed.Methods Primary triple negative breast cancer tumors were stained for cytosolic single-stranded DNA (ssDNA) using multiplex immunohistochemical staining. To increase cytosolic ssDNA, we genetically silenced TREX1. The role of tumor cytosolic ssDNA in promoting tumor immunogenicity and antitumor immune response was evaluated using murine breast cancer models.Results We found the tumorous cytosolic ssDNA is associated with tumor-infiltrating lymphocyte in patients with triple negative breast cancer. TREX1 deficiency triggered a STING-independent innate immune response via DDX3X. Cytosolic ssDNA accumulation in tumors due to TREX1 deletion is sufficient to drastically improve the efficacy of ICB. We further identified a cytosolic ssDNA inducer CEP-701, which sensitized breast tumors to ICB without the toxicities associated with inhibiting DNA damage response.Conclusions This work demonstrated that cytosolic ssDNA accumulation promotes breast cancer immunogenicity and may be a novel therapeutic strategy to improve the efficacy of ICB with minimal toxicities.